An Investigation of Pantograph Parameter Effects for Pantograph-Catenary Systems - Karakose, Ebru; Genoglu, Muhsin Tunay (Ieee, 2014)
The pantograph and the catenary perform the current collection process in electrical railway systems. In such systems, the main purpose is to improve the quality of current collection. Many factors and parameters can affect the interaction between the pantograph and the catenary. Internal or external factors affect the dynamic behavior of the system and lead to parameter variations. In practical applications, the system parameters can be changed very quickly. Therefore, the sensitivity of the system corresponding to the parameter variations is very important. In this study, the effects of parameter variations of pantograph on the system were investigated for the pantograph-catenary system. The system response caused by the parameter variations was examined for a constant reference contact force. Simulation studies were performed in Matlab-Simulink. The new transfer function was obtained by keeping the other parameters fixed in each parameter variation. The simulation result obtained by the new transfer function was compared with the simulation result of reference value. A parameter variation impact on the system response was also interpreted by comparing it with other parameter variations. After analyzing the effects of parameters on the system response, modeling can be accomplished by determining the appropriate control techniques. However, instead of setting the controller parameters for each parameter variation, the use of active control techniques would be more appropriate.
IEEE International Symposium on Innovations in Intelligent Systems and Applications (INISTA) -- JUN 23-25, 2014 -- Alberobello, ITALY
Keywords: pantograph; catenary; parameter variation